2018
DOI: 10.1016/j.repbio.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Supplementing in vitro embryo production media by NPPC and sildenafil affect the cytoplasmic lipid content and gene expression of bovine cumulus-oocyte complexes and embryos

Abstract: In our study, we added natriuretic peptide type C (NPPC) and/or sildenafil during in vitro maturation (IVM) of bovine cumulus-oocyte complexes (COCs) followed by in vitro culture (IVC) of embryos with or without sildenafil. We evaluated the effects on the lipid content (LC) of oocytes and embryos and also verified the expression of 96 transcripts related to competence in matured COCs and 96 transcripts related to embryo quality in blastocysts. After IVM, LC was decreased in oocytes by NPPC while sildenafil did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Embryos were produced in vitro from cumulus-oocytes complex from antral follicles of slaughtered cows based on the protocol previously published [50]. On the day 7 of in vitro culture (day 0 was on in vitro insemination), the embryos were recovered from the culture.…”
Section: Methodsmentioning
confidence: 99%
“…Embryos were produced in vitro from cumulus-oocytes complex from antral follicles of slaughtered cows based on the protocol previously published [50]. On the day 7 of in vitro culture (day 0 was on in vitro insemination), the embryos were recovered from the culture.…”
Section: Methodsmentioning
confidence: 99%
“…Embryos were produced in vitro from the cumulus-oocytes complex from the antral follicles of slaughtered cows based on the protocol previously published [51]. On days 7 to 8.5 of in vitro culture (day 0 was in vitro insemination), the embryos were recovered from the culture.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have shown that manipulating the level of cGMP with CNP in the maturation medium decreases the lipid content in the oocyte 22 . Lipolysis results from the sequential activity of adipose triglyceride lipase (ATGL), hormone-sensitive lipase (HSL), and mono-acyl glycerol lipase (MAG) 23 .…”
Section: Introductionmentioning
confidence: 99%
“…Activation of ATGL plays key role in initiation of lipolysis 24 . Also, perilipin (PLIN2) and diacylglycerol acyltransferase 1 (DGAT1) are required for the accumulation and stability of the LDs 22 . Higher cytoplasmic lipid content observed in in vitro produced (IVP) embryos in compare to their in vivo counterparts is one of the factors responsible for their lower cryosurvival rate 25 , 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation